Persistent Congenital Tibial Pseudoarthrosis until Adulthood Treated with Vascularised Fibular Graft: A 17-year Follow-up - Sitthiphong Suwannaphisit; Kenji Kawamura; Shohei Omokawa (Journal of Plastic and Reconstructive Surgery)
A 39-year-old woman diagnosed with persistent congenital tibial pseudoarthrosis until adulthood presented with a right leg angular deformity, associated pain, and significant limb length discrepancy. Over a 17-year period, the case was closely monitored and treated through excision of the pseudarthrosis, vascularised fibular graft with bone marrow-derived and cultured mesenchymal cells, combined with highly purified β-tricalcium phosphates, internal fixation, and the application of a ring Ilizarov fixator. The successful union of bones and correction of deformities was achieved through consideration of both mechanical and biological aspects.